The PHARMACY AND ARCHIPELAGO CON PHARMACY AND ARCHIPELAGO CONSTITUTIONAL THEORY: PHARMACY AS GUARDIAN OF ETHICAL AND LOCAL LEGAL BALANCE: FARMASI DAN TEORI KONSTITUSI NUSANTARA: APOTEKER SEBAGAI PENJAGA KESEIMBANGAN ETIS DAN HUKUM LOKAL - Dita, Rahma Dita; Sudrajat, Hendra (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2025)
This article explores the role of pharmacists as ethical and legal mediators within pluralistic legal systems in Indonesia. Informed by the theory of Konstitusi Nusantara (Nusantara Constitution), this study frames the pharmacist not merely as a medical professional but as a guardian of balance between local customs and national regulations. Using a qualitative normative-juridical method and interdisciplinary analysis across pharmaceutical sciences, constitutional law, and health anthropology, this research draws from literature and regional practices in Papua, Kalimantan, and Nusa Tenggara. Findings show that pharmacists often navigate overlapping norms professional codes, state law, and local customary systems especially when working within indigenous communities. Their unique position enables them to build culturally respectful communication, advocate for the safe use of traditional remedies, and promote ethical healthcare grounded in local wisdom. The study calls for curricular reform in pharmacy education that integrates local legal-cultural knowledge and for policies that institutionalize collaboration between pharmacists and customary authorities. This research provides conceptual and practical insights for building inclusive, locally rooted healthcare governance in Indonesia. Keywords: Pharmacist, Local wisdom, Legal pluralism, Indigenous health